2006
DOI: 10.2174/156802606778194190
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Carriers: A Strategy for Constructing Antigenic/Immunogenic Conjugates

Abstract: The rational design of artificial carriers for anchoring multiple copies of B and/or T cell epitopes, built-in vaccine adjuvants and "promiscuous" T cell epitopes for the construction of conjugates as antigenic substrates or potent immunogens has been the stimulus of intensive efforts nowadays. The unambiguous composition, the reliability and the versatility of the production of reconstituted antigens or immunogens has found a great number of biochemical applications in developing immunoassays of high sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 115 publications
(159 reference statements)
0
24
0
1
Order By: Relevance
“…As illustrate in Fig. (1), different chemistries to Chimeric peptides [38][39][40][41][42][43][44] Branched polymeric peptides poly[Lys(Ser i-DL -Ala m )] (SAK) [45][46][47] Sequential oligopeptide carriers (SOCn) [48][49][50][51][52] Multiple Antigenic Peptides (MAPs) [53,56,58,[60][61][62][63][64][65][66][67][68] Cyclic peptides [18,27,69,70] …”
Section: Chemical Derivatization Of Synthetic Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrate in Fig. (1), different chemistries to Chimeric peptides [38][39][40][41][42][43][44] Branched polymeric peptides poly[Lys(Ser i-DL -Ala m )] (SAK) [45][46][47] Sequential oligopeptide carriers (SOCn) [48][49][50][51][52] Multiple Antigenic Peptides (MAPs) [53,56,58,[60][61][62][63][64][65][66][67][68] Cyclic peptides [18,27,69,70] …”
Section: Chemical Derivatization Of Synthetic Peptidesmentioning
confidence: 99%
“…As reported by Sakarellos et al the repetitive Lys-Aib-Gly (SOC(n)-I) and Aib-Lys-Aib-Gly (SOC(n)-II) units adopt 3(10)-helical structures, while the SOC(n)-conjugates retain their original active conformations and they neither interact to the carriers nor to each other [49]. The helicoid structure of SOC(n) helps the reconstitution and/or mimicking of the native forms of the epitopes so that potent antigens are generated for developing specific, sensitive and reproducible immunoassays [50][51][52].…”
Section: E Branched Polymeric Peptidesmentioning
confidence: 99%
“…Sequential oligopeptide carrier (SOC 4 ), formed by the repetitive Lys-Aib-Gly moiety, is applied to display analyzed peptides [22]. The synthetic procedure starts with the step-by-step couplings of the protected residues (Boc/Bzl) corresponding to the SOC 4 carrier to the resin.…”
Section: Peptide Conjugates Synthesismentioning
confidence: 99%
“…SOC n is a sterically constrained scaffold, characterized by a few conformations in solution, comprising α‐aminoisobutyric acid (Aib), a strongly helicogenic C α ‐tetrasubstituted amino acid. It was found that the helical conformation of the tetrameric SOC 4 attributed mainly to the inclusion of Aib, induces a favorable arrangement of the conjugated epitopes, which retain their initial ‘active’ conformation and their potential for generating site‐specific immune responses9–12.…”
Section: Introductionmentioning
confidence: 99%